Media Pembelajaran Word Wall dalam Meningkatkan Keterampilan Berbicara Bahasa Jerman - Egidya Elyas Putri; Nurming Saleh; Jufri Jufri (Phonologie : Journal of Language and Literature, 2021)
Abstract. This research is Classroom Action Research which consists of two cycles. This study aims to determine the planning, process, and results of Word Wall Learning Media in improving German speaking skills of students of class XI IBB 1 SMA Negeri 1 Polewali. This research data consists of quantitative data and qualitative data. Quantitative data was obtained through the results of the speaking skills test in cycle I and cycle II and qualitative data was obtained through observation. The data were analyzed using the percentage technique. The results showed the average score obtained by students in the first cycle reached 58.26% and the second cycle reached 84.73%. These results indicate that the use of Word Wall learning media improves the German speaking skills of class XI IBB 1 students of SMA Negeri 1 Polewali.